Relief and Rescue: Suspensions and Elasticity in Financial Regulation, and Lessons from the UK's Management of the COVID-19 Pandemic Crisis - Iris H-Y Chiu; Andreas Kokkinis; Andrea Miglionico (Washington University Journal of Law & Policy, 2021)
This Article analyzes the UK’s approach to handling the economic impact of COVID-19, offering insight for developed financial jurisdictions embarking on regulatory suspensions. When existing law no longer meets overarching policy goals such as financial stability, regulators resort to the theorization of legal elasticity. This Article situates regulatory suspension within this theory analyzing the tensions, hazards, and accompanying decision-making frameworks. The authors make three proposals for deployment of legal elasticity by regulators: (1) evaluate institutional stability; (2) engage in relational paradigms with relevant agencies, entities, and stakeholders; and (3) establish ex ante frameworks for crisis management and the potential use of legal elasticity.
Keywords: COVID; COVID-19; coronavirus; coronavirus pandemic; pandemic; UK; United Kingdom; economy; economic; economic impact; finance; financial; regulation; regulatory; elasticity